Description of Cognitive Function in The Elderly with Puzzle Therapy Intervention: Case Study - Setiawan Setiawan; Neng Ikhtiyarotul Fikriyah; Dadang Purnama (Genius Journal, 2023)
The elderly can experience a decrease in cognitive function because the body functions of the elderly also tend to decrease. Cognitive disorders in the elderly can interfere with and affect the behavior or activities of the elderly. The role of nurses is very important to provide interventions that can improve the cognitive function of the elderly. Non-pharmacological efforts are needed to overcome cognitive function problems in the elderly, one of which is through puzzle therapy. Puzzles in the form of pictures in the form of small pieces to hone intelligence, lead to patience, introduce the ability to share, and are a fun way to train the brain, especially for the elderly. This research method is a case study method with a nursing care approach to the elderly aged 80 years, the MMSE and SPSMQ questionnaires are used to assess cognitive and intellectual development in the elderly. The results showed that the application of puzzle therapy which had been carried out for 6 meetings with an intensity of 1x20 minutes per day showed an improvement in the results of the MMSE and SPSMQ scores, in other words there was an increase in cognitive and intellectual function in the elderly. For maximum results, puzzle preparation exercises should be carried out regularly and can be done together in nursing homes so that the elderly are more motivated and more enthusiastic.